Pengaruh Penambahan Sari Jeruk Nipis (Citrus aurantifolia) sebagai Bahan Penggumpal Alami terhadap Karakteristik Fisik dan Kimia Tahu Kacang Hijau (Vigna radiata) - Bhakti Etza Setiani; V. Priyo Bintoro; Rifqi Nur Fauzi (Faculty of Agricultural Technology, Universitas Semarang, 2021)
Tofu is a product made by beans protein coagulation. The food is relatively cheap, much preferred by all levels of society and highly nutritious. The main nutrient of tofu is protein. This study aims to determine the characteristics of green beans tofu added by lime juice as a completing material and further more, this study also the optimal time aimed to determine presipitate for coagulating green bean protein. The research was conducted in Food Engineering Laboratory and Laboratory of Food and Nutrition Chemistry Faculty of Animal Husbandry and Agriculture Sciences Diponegoro University from March 2017 - May 2017. The experimental design used in this study using Randomized Complete Design (RCD) with 3 treatments and 7 repetitions By treatment of concentration of addition of lemon juice there were 5% for T1, 10% for T2, and 15% for T3. The total water content, total protein content, and texture test results would tested with Analysis of Variance (ANOVA) with a significance level of 5%. If there is any effect of treatment, it would be continued with Duncan Double Area Test. The results showed that the increasing concentration of lime juice would result in a total water content of 85 % - 72 %, total protein content of 11.98 % to 8.74 % , textures from 129.61 N - 194.00 N, and the total yield content of 15.20 % - 39.73%.